Te aho tapu uru tapurua o te muka e tui nei ā muri, ā mua: The Sacred Strand That Joins the Past and Present Muka Strands Together - Taituha, Gloria (Auckland University of Technology, 2021)
This is an exegesis with a shared collaborative creative component with two other weaving exponents, Jacqueline McRae-Tarei and Rose Te Ratana which is reflective of a community of shared practice. This shared practice and subsequent collaborative creative component will be based on the overarching theme of the written component, a synthesis of philosophy, tikanga rangahau (rules, methods), transfer of knowledge and commitment to the survival of ngā mahi a te whare pora (ancient house of weaving) in a contemporary context. The sole authored component and original contribution to knowledge for this project is the focus on the period of 1860 – 1970, which will be referred to as Te Huringa. The design of this exegesis will be informed by Kaupapa Māori Ideology and Indigenous Methodologies. Te Huringa, described as the period from first contact with Pākehā settlers up until the Māori Renaissance in the 1970s. After the signing of the Treaty, the settler population grew to outnumber Māori. British traditions and culture became dominant, and there was an expectation that Māori adopt Pākehā culture (Hayward, 2012, p.1). This period, also defined, as the period of mass colonisation, saw the erosion of traditional Māori society including the status of raranga as a revered art form. The creative component will be a Whakaaturanga, an expression of taonga Māori (precious Māori artefacts) with a focus on whāriki (woven mat), whatu muka (finger weaving) and tāniko (another form of finger weaving). This work can be stand-alone, but can also sit within the wider, collaborative Whakaaturanga to create a broader conceptual design of the origins of raranga, whatu muka and tāniko.
Keywords: Raranga; Kairaranga; Weaving; Te Whare Pora